2022
DOI: 10.1001/jamanetworkopen.2022.36364
|View full text |Cite
|
Sign up to set email alerts
|

Association of Attention-Deficit/Hyperactivity Disorder Diagnosis With Adolescent Quality of Life

Abstract: ImportanceAppropriate diagnosis of attention-deficit/hyperactivity disorder (ADHD) can improve some short-term outcomes in children and adolescents, but little is known about the association of a diagnosis with their quality of life (QOL).ObjectiveTo compare QOL in adolescents with and without an ADHD diagnosis.Design, Setting, and ParticipantsThis cohort study followed an emulated target trial design using prospective, observational data from the Longitudinal Study of Australian Children, a representative, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…We retrieved 3133 unique records, of which 200 were included in the review (Figure 1). All reasons for excluding records after full-text review are given in eAppendix 6 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We retrieved 3133 unique records, of which 200 were included in the review (Figure 1). All reasons for excluding records after full-text review are given in eAppendix 6 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
“…Seventy studies (35%) reported in the title that the study aimed to emulate a target trial; 180 (90%) did so in the Methods section. Twenty studies (10%) reported the study was prospectively registered, 16 of these 20 (80%)…”
Section: Resultsmentioning
confidence: 99%
“…Children with medicalized behaviors are “railed” into certain ways of responses to those behaviors. Findings from a recent cohort study suggest that an ADHD diagnosis in childhood may not result in any improvements in quality-of-life measures in adolescents and may even negatively impact some outcomes, including the risk of self-harm ( 33 ). Second, the relative age effect phenomenon also concerns the pharmacological treatment for ADHD [see, for a review, ( 34 )].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Erlandsson et al expect that the vast majority of research on inattentive and hyperactive child behaviors will continue to rest on scientifically unjustifiable assumptions about children's attributes. The unequal allocation of resources available in contemporary ADHD research is worrisome, especially considering recent research indicating the potential negative effects of the ADHD label ( 8 ) and its treatment ( 9 ).…”
mentioning
confidence: 99%